1997
DOI: 10.1093/molehr/3.12.1037
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C plays an important role in the human zona pellucida- induced acrosome reaction

Abstract: To investigate the involvement of protein kinases in signal transduction in the human zona pellucida (ZP)-induced acrosome reaction (AR), the effects of protein kinase (PK) activators, dibutyryl cAMP (PKA) and cGMP (PKG), phorbol 12-myristate 13-acetate (PMA, PKC), and the PKC inhibitor, staurosporine were studied. Sperm samples were obtained from normozoospermic men with normal sperm-ZP binding. Oocytes were obtained from other patients with failure of fertilization in vitro. Motile spermatozoa selected by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…In severe teratozoospermic subfertile men, defective ZPIAR is more likely to be related to major structural defects of the sperm head, such as small or abnormal acrosomes, or associated abnormalities in the overlying plasma membrane. By contrast, in men with normal sperm morphology, defective ZPIAR is most likely to be due to subtle biochemical or molecular defects in ZP receptors, signal transduction pathways, inefficient cholesterol or zinc removal from the plasma membrane during capacitation, actin polymerization or acrosomal enzyme activation [36][37][38][39][40][41][42]. Several in vitro studies have shown that zinc and SP inhibit sperm capacitation, including hyperactivation and AR, as well as spermatozoa-ZP binding and penetration [17,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In severe teratozoospermic subfertile men, defective ZPIAR is more likely to be related to major structural defects of the sperm head, such as small or abnormal acrosomes, or associated abnormalities in the overlying plasma membrane. By contrast, in men with normal sperm morphology, defective ZPIAR is most likely to be due to subtle biochemical or molecular defects in ZP receptors, signal transduction pathways, inefficient cholesterol or zinc removal from the plasma membrane during capacitation, actin polymerization or acrosomal enzyme activation [36][37][38][39][40][41][42]. Several in vitro studies have shown that zinc and SP inhibit sperm capacitation, including hyperactivation and AR, as well as spermatozoa-ZP binding and penetration [17,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Close association of IP 3 R and GCR in sperm membrane supports the suggestion made by Suarez and coworkers that IP3 mediated release of Ca 2+ from calmodulin stores is related to the control of gated calcium channels during sperm motility and hyperactivated motility Suarez, 2001, 2003). These processes may also be operational during fusion of sperm with oocyte membranes at the time of fertilization (Liu andBarker 1997, Revelli et al, 2002). The role of GC is well defined and several studies confirm that GC regulates not only the gated Ca 2+ channel but it also plays an important role as a chemotactic agent during sperm oocyte fusion in sea urchin (Santos-Sacchi and Gordon 1980, , Cohen-Dayag et al, 1995.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some have shown that components of the egg zona pellucida are responsible for the acrosome reaction, but similarly the older drug inhibitor of PKC, Staurosporine, blocks the acrosome reaction (Liu and Baker, 1997).…”
Section: Spermmentioning
confidence: 99%